The Effect Of Using Differentiated Instruction On Learning Breaststroke In Female Students College of Physical Education and Sport Sciences - Ahmed, Iftikhar (Journal of Physical Education, 2016)
The aim of the research is to identify the effect of using differentiated instruction in learning breast stroke in sophomore female students of the college of physical education and sport sciences. The researchers used the experimental method on (28) female students of the academic year 2015 – 2016. The teaching session consist of four weeks differentiated instruction in teaching breaststroke. The data was collected and treated using proper statistical operations to come up with the results. The researchers concluded that using differentiated instruction teaching style lead to better learning of breaststroke. Finally the researchers recommended using updated teaching styles in order to teach learners using the best styles suitable for their individual needs.